2019
DOI: 10.1016/j.jid.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch Exacerbates Psoriasis by Stimulating Keratinocyte Proliferation and Cytokine Production

Abstract: Psoriasis is a chronic inflammatory autoimmune skin disease that often occurs in rubbed areas undergoing a strong mechanical stretch, such as the elbows and knees. However, the pathologic role of mechanical tension in psoriasis remains unclear. In this study, we investigated the contribution of keratinocyte mechanical stretch to the clinical features of psoriasis. We found that keratinocyte proliferation and skin barrier-associated gene expression increased significantly after 24 hours of continuous stretching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 28 publications
1
57
0
Order By: Relevance
“…Hollox et al showed a significant association between higher genomic copy number for hBD genes and risk of psoriasis [73]. Qiao et al reported that the production of hBD and another AMP, LCN2, increased significantly in keratinocytes following mechanical stretch [74]. In addition, Bhatt et al showed that sustained secretion of S100A7 from differentiated keratinocytes is dependent on the downregulation of caspase-8, and that IL-1α is necessary and sufficient to induce S100A7 secretion [75].…”
Section: Keratinocytes and Ampsmentioning
confidence: 99%
“…Hollox et al showed a significant association between higher genomic copy number for hBD genes and risk of psoriasis [73]. Qiao et al reported that the production of hBD and another AMP, LCN2, increased significantly in keratinocytes following mechanical stretch [74]. In addition, Bhatt et al showed that sustained secretion of S100A7 from differentiated keratinocytes is dependent on the downregulation of caspase-8, and that IL-1α is necessary and sufficient to induce S100A7 secretion [75].…”
Section: Keratinocytes and Ampsmentioning
confidence: 99%
“…Cutaneous injury activates toll-like receptor 3 in keratinocytes to produce various proinflammatory cytokines, such as TNF-α, IL-6, and IL-36. The production of psoriasis-associated inflammatory cytokines can also be induced by mechanical stretches [ 52 , 53 ]. These studies confirm that cytokines produced by keratinocytes can play a significant role in the development of this condition, and that keratinocytes are important in the initiation of cutaneous inflammation by activating immune cells.…”
Section: Implication Of Keratinocytesmentioning
confidence: 99%
“…Treatment of keratinocytes with mechanical stimulation activates the secretion of inflammatory cytokines (IL-1α, IL-6, IL-23, and TNF) and chemokines (CXCL1 and CCL20) ( 64 – 66 ). Other studies have reported that mechanical stretching promotes keratinocyte proliferation and inhibits keratinocyte differentiation ( 65 , 67 , 68 ).…”
Section: Keratinocytes As Sentinels In Skin Immune Defensementioning
confidence: 93%